CosX+cosП-X+sinX = 0sinП+Х — cosП/2-X = корень из трех

cosX+cos(П-X)+sinX = 0

sin(П+Х) - cos(П/2-X) = корень из трех

     

     x= (-1)^(n+1) П /3 +  Пk  

     

     

     

  • 1. cosX+cos(П-X)+sinX = 0

    -2sinx= √ 3 

        sinX = 0

       cosX-cosХ+sinX = 0

     

     

    2.sin(П+Х) - cos(П/2-X) = √ 3

     

     

     

         X= ПK

     

     

     

     

    x= (-1)^(n+1)  arcsin √ 3 /2+  Пk 

     

     

    - sinХ - sinX = √ 3 

     

     

     

    sinx=- √ 3 /2

    x=(-1)^n  arcsin( - √ 3 /2)+  Пk